2019
DOI: 10.1021/acs.jpcc.8b12545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Structure on the Electrochemical Cleavage of Alkoxyamines

Abstract: A test set of 14 TEMPO-based alkoxyamines was studied via a combination of cyclic voltammetry (CV) and accurate quantum chemistry to assess the effect of substituents on electrochemical cleavage. The experimental oxidation potentials of the alkoxyamines fell into the range of 1.1-1.6 V versus Ag/AgCl in acetonitrile, were well reproduced by theory (MAD 0.04V), with values showing good correlation with the sR Hammett parameters of both the R group and the OR group in TEMPO-R. Importantly, most of the studied al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 29 publications
(76 reference statements)
2
60
0
Order By: Relevance
“…Synthesis of TEMPO-iPr. TEMPO-iPr was prepared in an analogous fashion to that described previously, 22 to give a colourless oil; 1 H NMR (400 MHz; CDCl3) 3.98 (sept, J = 6.2 Hz, 1H), 1.45-1.10 (m, 6 x CH3 and 3 x CH2, 24H); 13 Computational Procedures. All standard ab initio molecular orbital theory and density functional theory (DFT) calculations were carried out using Gaussian 09 28 and Molpro 29 software packages.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of TEMPO-iPr. TEMPO-iPr was prepared in an analogous fashion to that described previously, 22 to give a colourless oil; 1 H NMR (400 MHz; CDCl3) 3.98 (sept, J = 6.2 Hz, 1H), 1.45-1.10 (m, 6 x CH3 and 3 x CH2, 24H); 13 Computational Procedures. All standard ab initio molecular orbital theory and density functional theory (DFT) calculations were carried out using Gaussian 09 28 and Molpro 29 software packages.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…To better understand the factors involved in alkoxyamine cleavage, we explored the CV behavior of a TEMPO-based alkoxyamine, TEMPO-i-Pr. This species showed partially reversible oxidation and a slower kfrag (~ 0.3 s −1 ) in acetonitrile with TBAClO4 electrolyte, 22 and thus is a good candidate for manipulation based on the reaction conditions. In conjunction with this experimental work, we used high-level calculations to study the effect of different electrolytes and solvents on this process.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with experimental observations for the oxidative cleavage of the corresponding TEMPO-based analogues. [12][13][14][15] If the results above were to apply also to corresponding the excited state mesolytic cleavage, it would suggest styrene actually undergoes photoinitiated cationic polymerization with this PNMP agent (which would still be consistent with the observed control), and the acrylates in particular struggle to undergo cleavage at all, which could help to explain the failed experiments with this monomer. While most of the trends in the calculations of Figure 3 would be mirrored in the excited state mesolysis energies, there are two important differences: (1) the excited states are higher in energy and this additional energy can help to overcome the otherwise unfavorable Gibbs free energies requirements;…”
Section: Figurementioning
confidence: 73%
“…Experiments have shown that the exact specific cleavage behavior depends on the leaving group and the presence or absence of nucleophiles including coordinating solvents such as acetonitrile (see Scheme 3). [12][13][14][15] As seen in Scheme 3, in the oxidized species at least, cleavage to a carbon-centered radical is expected for acrylate and methacrylate polymerizations, but not for styrene which will produce carbocations. 12 Summing up, while it has been assumed until now that PNMP proceeds via energy transfer and standard homolytic cleavage, the possibility of mesolytic cleavage and its implications has not been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation